UPAYA PENGELOLA PKBM UNTUK MENINGKATKAN KEMANDIRIAN WARGA BELAJAR KESETARAAN PAKET C MELALUI KEWIRAUSAHAAN - Cecep Wahyudin; Nunu Mahmud Firdaus (Comm-Edu (Community Education Journal), 2018)
PKBM is an institution that focuses on education development in the non-formal field. The researcher analyzes the management of PKBM management on the quality aspects of the students who are coached in the PKBM. This research formulates the problem of management and implementation patterns in students and the output of students who are fostered. The method used by the researcher is a descriptive method by using observation guidelines as a measuring tool and using the PKBM research object and students. The results of this study found that the planning of vocational training activities for PKBM learning residents, all (100%) answered very well there was planning before the program activities carried out so that those who answered there was no need for planning, mediocre and incomprehensible none answer (0%).